Synchronization of an On-Board Photovoltaic Converter Under Conditions of High Dynamic Voltage Frequency Change - Tomasz Binkowski; Ľubomír Beňa; Dušan Medveď; Paweł Pijarski (Energies)
The decarbonization of energy systems is forcing the development of renewable energy generation and consumption technologies. Photovoltaic systems are being used in almost every industry, including autonomous power systems used on ships, space vehicles, or flying platforms, where the voltage supplying specific equipment can change in an overridingly controlled manner. Feeding energy from a renewable source into a power system with highly dynamic frequency changes is not possible for traditional grid converter control strategies. This is caused by the synchronization system, which is designed for a fixed value of the grid voltage frequency, and by the proportional-resonant controllers used. In this paper, it is shown that frequency tracking correction causes deviations from the unit amplitude of synchronization signals, causing errors in the reference signals responsible for the active and reactive components of the converter current. To solve this problem, a new variable frequency adaptation system using a generalized second-order integrator was proposed. As a result, synchronization signals of unit amplitude were obtained. Due to the proposed method, the proportional-resonant controller was able to control the active and reactive components of the current even when the voltage frequency changes, adjusting the resonant frequency.